Alterations of Obestatin, Cardiac Markers and Lipid Profile Levels in Type 2 Diabetes Mellitus - Balaky, Hazhar M.; Kakey, Ismail S. (Iraqi Journal of Science, 2021)
The current investigation aimed to test the alterations of the levels of obestatin hormone, lipid profile and cardiac function markers in relation to hyperglycemia in patients with non-insulin diabetes mellitus. The study included 118 diabetic subjects (56 males, 62 females) and 60 healthy non-diabetic subjects (30 males, 30 females). Diabetic and healthy subjects were age-matched. Serum levels of obestatin, lipid profile markers including total cholesterol (STC), triglycerides (STG), low and high density lipoproteins (LDL-C and HDL-C), as well as cardiac function markers including, creatine kinase and lactate dehydrogenase enzymes were determined in all subjects. The findings revealed a remarkable decrease in the level of serum obestatin in both diabetic males and females with both age ranges (40-59 and 60-80 years). On the other hand, the results showed that serum STC, LDL-C, and STG levels were statistically significantly elevated, while that for HDL-C was significantly decreased in diabetic males and females with both age ranges. Concerning the cardiac markers, the results found out that the levels of CK-MB and LDH were significantly increased in type 2 diabetic males and females with both age ranges. The results suggested that a low concentration of obestatin is a significant risk factor for type 2 DM, with a key role for this hormone in the pathogenesis. Accordingly, altered levels of obestatin could be used as an important indicator for type 2 DM. The current study also suggests a direct relationship between lipid profiles, except for HDL, the decreased obestatin level, the increased cardiac function markers, and hyperglycemic status in type 2 DM.